The Dutch Republic : its rise, greatness and fall, 1477-1806 - Israel, Jonathan Irvine (Oxford : Clarendon Press, 1995)
The Dutch Golden Age - the age of Grotius, Spinoza, Rembrandt, Vermeer, and a host of other renowned artists and writers, was also remarkable for its immense impact in the spheres of commerce, finance, shipping, and technology. It was in fact one of the most spectacularly creative episodes in the history of the world. In this book, Jonathan Israel gives the definitive account of the emergence of the United Provinces as a great power, and explains its subsequent decline in the eighteenth century. He places the thought, politics, religion, and social developments of the Golden Age in their broad context, and examines the changing relationship between the northern Netherlands and the south, which was to develop into modern Belgium. One of the principal aims of the book is to provide a new type of integrated history which draws the different dimensions of the discipline firmly together in strictly non-technical language. The result is a comprehensive and lucid account as useful to the reader primarily interested in artistic and cultural history as to the student who needs a survey of the Republic's institutions, class structure, and economic development. At the same time it will provide an invaluable aid to scholars interested in new research and new interpretations.
1. Introduction -- 2. On the Threshold of the Modern Era. The Rise of Holland. Under the Burgundians. The Early Habsburg Netherlands. The Institutions of the Habsburg Netherlands -- 3. Humanism and the Origins of the Reformation, 1470-1520 -- 4. Territorial Consolidation, 1516-1559 -- 5. The Early Dutch Reformation, 1519-1565. The Netherlands Church on the Eve of the Reformation. The Impact of Luther. Fragmentation. Spiritualism and the Impact of Persecution. The Rise of Calvinism -- 6. Society before the Revolt. The Land, Rural Society, and Agriculture. Urbanization. The Urban Economy. Institutions of Civic Life: Guilds, Militias, Chambers of Rhetoric. Poverty and Civic Welfare. The Regents -- 7. The Breakdown of the Habsburg Regime, 1549-1566. The Seeds of Revolt. Crisis, 1559-1566 -- 8. Repression under Alva, 1567-1572 -- 9. The Revolt Begins -- 10. The Revolt and the Emergence of a New State. The Revolt Survives, 1573-1575. From the Pacification of Ghent (1576) to the Union of Utrecht (1579). The Two Netherlands. The Habsburg Reconquest of the South, 1579-1585. The North Netherlands under Leicester, 1585-1587 -- 11. Consolidation of the Republic, 1588-1590 -- 12. The Republic Becomes a Great Power, 1590-1609. Territorial Expansion. The Fixed Garrison System. The Dutch Military Reforms and their European Significance. The Dutch in Europe: Skills, Technology, and Engineering -- 13. The Institutions of the Republic. The Provinces. Taxation and the Tax System. The Generality. The Generality Lands. The Stadholderate -- 14. The Commencement of Dutch World Trade Primacy. Revolt, Commerce, and Migration from the South. The Changing Balance between 'Bulk-Carrying' and the 'Rich Trades'. The Beginnings of the Dutch Colonial Empire -- 15. Society after the Revolt. Urbanization. Rural Society. The Nobility. The Regents. The Merchant Elite. The Elite of the Skilled. Wages. Civic Poor Relief and Charitable Institutions -- 16. Protestantization, Catholicization, Confessionalization. The Confessional Arena. The Organization of the Dutch Reformed Church. The Rejection of Toleration. The Catholic Revival. Confessionalization and the State. Anabaptism and the Confessionalization Process -- 17. The Separation of Identities: The Twelve Years Truce. The Pressure to Negotiate. The Political and Economic Consequences of the Truce. 'South' confronts 'North' -- 18. Crisis within the Dutch Body Politic, 1607-1616 -- 19. The Fall of the Oldenbarnevelt Regime, 1616-1618 -- 20. The Calvinist Revolution of the Counter-Remonstrants, 1618-1621. Domestic Politics. The Synod of Dordrecht (Dordt), 1618-1619. Maurits, the Counter-Remonstrants, and the Commencement of the Thirty Years War. The Beginnings of the Further Reformation -- 21. The Republic under Siege, 1621-1628. Maurits's last Years, 1621-1625. The Commencement of Frederik Hendrik's Stadholderate. Politics, Ideology, and the Great Dutch Toleration Debate of the late 1620s -- 22. The Republic in Triumph, 1629-1647. Frederik Hendrik Victorious and the Regents Divided, 1629-1632. The Negotiations between North and South of 1632-1633. Frederik Hendrik and the Regent Party-Factions, 1633-1640. The Contest for the Leadership of the Republic, 1640-1647 -- 23. Art and Architecture, 1590-1648. The Proliferation of Art. Architecture and the Building Boom. Specialization in Painting. The Second Phase in Golden Age Art, 1621-c.1645 -- 24. Intellectual Life, 1572-1650. The Forming of a New Culture. Universities and Civic High Schools. Dutch Late Humanism. The Rise of the Mechanistic World-View. Boreelism and the 'Third Force' -- 25. The Stadholderate of William II, 1647-1650 -- 26. Society. The Economy. Population. Work and Migration. The Huguenot Influx. Wages and Living Standards. Rural Society -- 27. Confessionalization, 1647-1702. The Rise of Toleration. William III and the Churches. Jansenism and Anti-Jansenism. The Waning of the Lesser Churches. Church Politics in the Generality Lands. The Unity of the Public Church. Internal Confessionalization. The Later Stages of the Toleration Debate -- 28. Freedom and Order. A Disciplined Society. Schools, Literacy, and the Reshaping of Popular Culture. The Further Reformation and Society -- 29. The Republic at its Zenith, I: The 1650s. The Making of the 'True Freedom'. The First Anglo-Dutch War (1652-1654) and the Exclusion Crisis (1654). De Witt's System during the Later 1650s -- 30. The Republic at its Zenith, II: 1659-1672. 'South' and 'North' after the Peace of the Pyrenees, 1659. Party and Faction in the Early 1660s. Ideological Conflict in the Early 1660s. The Second Anglo-Dutch War, 1664-1667. The Republic in Conflict with Louis XIV. The Twilight of the 'True Freedom' -- 31. 1672: Year of Disaster -- 32. The Stadholderate of William III, 1672-1702. From the 'Year of Disaster' to the Peace of Nijmegen, 1672-1678. From Nijmegen to the Revocation of the Edict of Nantes, 1678-1685. The Republic and the Glorious Revolution, 1685-1691. The Last Years of William III's Stadholderate -- 33. Art and Architecture, 1645-1702. Urban Expansion, Town Planning, and the Arts. Phase Three: The Zenith in Painting, c.1645-1672. Art after the Crash of 1672 -- 34. Intellectual Life, 1650-1700. Intellectual Crisis. The Universities. Science. The Anti-Socinian Campaign. Radical Cartesians and Spinozists. The Death of the Devil. The Two Dutch Enlightenments -- 35. The Colonial Empire. The Territories. Commerce, Shipping, and Seamen in the Indies. Power, Politics, and Patronage. Religion and Discipline -- 36. The Republic of the Regents, 1702-1747. The New Regime. The War of the Spanish Succession, 1702-1713. The Austrian Netherlands and the North after 1713. Neutrality and Domestic Stability, 1713-1746 -- 37. Society. Economic Decline -- Relative and Absolute. Urban Decay. Wealth and Poverty -- 38. The Churches. Dutch Reformed, Protestant Dissenters, Catholics, and Jews. The Loosening of Internal Confessional Barriers -- 39. The Enlightenment. The Dutch Impact. The 'Radical' Enlightenment. The Decline of the Universities. The Decline of the Visual Arts. The Enlightenment in the Austrian Netherlands. The Enlightenment in the Colonial Empire. The Later Dutch Enlightenment -- 40. The Second Orangist Revolution, 1747-1751 -- 41. The Faltering Republic and the New Dynamism in the 'South'. Politics during the Minority of William V, 1751-1766. New Directions in the Austrian Netherlands. The Early Years of William V's Stadholderate, 1766-1780 -- 42. The Patriot Revolution, 1780-1787 -- 43. The Fall of the Republic. The Orangist Counter-Revolution, 1787-1795. The Conservative Revolution in the 'South' and the New 'Netherlands Republic'. The End of the United Provinces -- 44. Denouement. The Batavian Republic, 1795-1806. Abolished by Napoleon.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Netherlands -- History -- House of Habsburg, 1477-1556.; Netherlands -- History -- Eighty Years' War, 1568-1648.; Netherlands -- History -- 1648-1795.; Netherlands -- History -- Batavian Republic, 1795-1806.; Netherlands -- History; Pays-Bas -- Histoire; Pays-Bas -- Histoire -- 1477-1556 (Maison de Habsbourg); Pays-Bas -- Histoire -- 1568-1648 (Guerre de Quatre-Vingts Ans); Pays-Bas -- Histoire -- 1648-1795.; Pays-Bas -- Histoire -- 1795-1806 (République batave); HISTORY -- General; Netherlands; Niederlande; Machtpolitik; Politik; Politisches System; Unabhängigkeitskrieg; Wirtschaft; Republiek der Verenigde Nederlanden; Regions & Countries - Europe; History & Archaeology; Netherlands, Belgium & Luxembourg; Pays-Bas -- 1795-1806 (République batave); Pays-Bas -- Histoire; Pays-Bas -- Civilisation; Pays-Bas -- 17e siècle.; Pays-Bas -- 18e siècle.; HOLANDA -- HISTORIA -- CASA DE HABSBURG, 1477-1556.; HOLANDA -- HISTORIA -- GUERRAS DE LA INDEPENDENCIA, 1556-1648.; HOLANDA -- HISTORIA -- 1648-1795.; HOLANDA -- HISTORIA -- REPUBLICA BATAVIA, 1795-1806.; 1477-1806; History